Dentoalveolar Distalisation in Class III Skeletal Base Using Buccal Shelf Mini-implants - A Case Report - Khyati, Narula; Siddarth, Shetty (Orthodontic Journal of Nepal, 2019)
Before the advent of skeletal anchorage distalisation of the lower arch was considered cumbersome. Individual lower molar distalisation followed by retraction into the distalised space created is very time-consuming. Therefore, to reduce the treatment duration lower arch distalisation can be attempted by using buccal shelf screws. Here we present a case of Angle’s Class III malocclusion which has been treated effectively with distalisation of lower arch using 2 buccal shelf screws (2x12mm) with elastic chains following lower third molars extraction. We achieved full arch distalisation of 3.5mm bilaterally in a span of 1.5 months into a class I molar and canine relationship with normal overjet and overbite. Total treatment duration was of 17 months. These results were stable. There were no changes in vertical facial dimensions.